A baseline‐free and non‐contact method for detection and imaging of structural damage using 3D laser vibrometry. Issue 4 (10th June 2016) - Aryan, P.; Kotousov, A.; Ng, C. T.; Cazzolato, B. S.
Summary: Detection and characterisation of structural damage using guided waves is very promising technique in non‐destructive testing and structural health monitoring systems. Because of their simplicity and low cost, current techniques normally utilise traditional piezo‐electric or optical fibre sensors to capture a directional scattered field from a defect or damaged area. However, the practical implementation of these techniques usually requires an extensive preliminary study in order to identify a suitable location and polarisation of the sensors, as well as determine the optimal parameters for wave excitation, which vary depending on the size and type of damage and structure. Recent advances in 3D laser vibrometry provide an opportunity to avoid many of the restrictions and limitations associated with traditional (1D) sensing systems by capturing the transient 3D displacement/velocity fields rather than the displacement/strain along a single axis and limited to a small number of discrete locations. Using 3D laser vibrometry, this paper suggests a non‐contact, baseline‐free method for imaging structural defects such as corrosion spots, cracks and dents as well as delamination damage. It focuses on the mode conversion effects and investigates the sensitivity of the in‐plane and out‐of‐plane scattered fields in relation to the presence of common defects. The experimental measurements are presented in terms of the root mean square (RMS) values of the velocity field. The outcomes of the present study can help in a number of ways, including selecting an appropriate strategy for defect detection using guided wave techniques. Copyright © 2016 John Wiley & Sons, Ltd.